A novel hydrophilic amino acid ionic liquid [C2OHmim][Gly] as aqueous sorbent for CO2 capture. (March 2016) - Lv, Bihong; Xia, Yinfeng; Shi, Yun; Liu, Nan; Li, Wei; Li, Sujing
Highlights: A novel amino acid ionic liquid ([C2 OHmim][Gly]) was designed for CO2 capture. The reaction of [C2 OHmim][Gly] with CO2 followed the zwitterion mechanism. [C2 OHmim][Gly] owns a higher absorption capacity of 0.575 mol CO2 /mol absorbent. [C2 OHmim][Gly] has a great thermal stability and better resistance to O2 . Abstract: Since functionalized ionic liquid (ILs) could achieve excellent performance on CO2 capture by introducing suitable moieties in the conventional ionic liquids, design and synthesis of new ionic liquids have been attracting remarkable interests. In this work, we designed a novel hydrophilic amino acid ionic liquid ([C2 OHmim][Gly]) that was functionalized based on the imidazolium ionic liquid with glycine anions and hydroxy group for CO2 absorption. The absorption capacity of [C2 OHmim][Gly] was 0.575 mol CO2 /mol absorbent that was similar to the equimolar stoichiometry following the zwitterion mechanism. Simple synthesis, large absorption capacity, good resistance to O2, and high regeneration efficiency make this functionalized ILs great potential for making up the deficiencies of aqueous MEA, therefore benefiting industrial applications.